Peningkatan Keterampilan Petani dalam Menyusun Rencana Bisnis Usahatani Jagung di Desa Karang Rejo - Tika Leoni Putri; Astri Shabrina; Suci Amalia; Muhammad Sarifudin (Institut Agama Islam Ma’arif NU (IAIMNU) Metro Lampung, 2021)
Abstract Corn is a strategic agricultural commodity with high economic potential, particularly for rural communities in Indonesia. However, many corn farmers still lack basic skills in managing their farming enterprises as professional business units. Most of them focus solely on production without proper financial planning, risk analysis, or marketing strategies. This community service project was conducted in Karang Rejo Village, Central Lampung, with the primary objective of improving farmers’ capacity to develop structured and realistic farm business plans. The activity applied the Asset-Based Community Development (ABCD) approach, which emphasizes the use of local assets such as farming knowledge, land, social capital, and market access to promote sustainable community empowerment. The program consisted of participatory training, focused group discussions, and hands-on mentoring over three intensive sessions, followed by individual consultations. Training materials included SWOT analysis, cost–benefit calculations, business goal setting, and financial projections tailored to corn farming. Evaluation through pre-tests and post-tests showed that 75% of the participants improved their understanding and ability to develop business plans. In addition, 19 out of 22 farmers successfully completed a basic business plan independently by the end of the program. The results demonstrate that empowering farmers through context-based andragogical methods is effective in strengthening managerial skills and promoting a shift from traditional to entrepreneurial farming mindsets. This initiative also aligns with national agricultural modernization goals and provides a replicable model for other farming communities. Continued support and collaboration with local stakeholders are recommended to ensure the sustainability of the outcomes. Keywords: corn farming, business plan, rural empowerment, ABCD approach, agricultural extension, community engagement